Gestão por indicadores na construção civil: estudo de benchmarking - Ortega, Carlos Henrique (2014)
The willing of this thesis is to present the current stage of construction, that means a fierce competition, and the way of management based by indicators. So in conjunction with indicators exist Benchmark, which is a method of evaluating comparative by the companies. The system of management by indicators is the basis to set targets, showing the company's past and its future prospects being able to support this new position in the market. Thus, the focus of this work is the analysis of the applicability of the method of benchmarking, developed by the Center for Innovation Oriented Building (NORIE / UFRGS). Therefore offered a picture of reality by means of the method of benchmarking, categorizing indicators and putting in numbers complex facts of the process of the construction industry, not aiming to rank the companies.